The Influence Of Transformational Leadership And Motivation On Employee Performance In Coffeehouse Business - Abdillah, Afif; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to explore how organizational culture and interpersonal communication impact employee performance, focusing on the XYZ company in the oil and gas industry. The research adopts an associative approach using quantitative methods. A sample of 66 respondents was conveniently selected from a population of 152 within the company. The participants, current employees of XYZ company, responded to a Likert scale questionnaire ranging from 1 to 5. Statistical Package for the Social Sciences (SPSS) was used for validity, reliability, and classical assumption tests. Multiple linear regression tests were applied for data analysis, and hypothesis testing was conducted for both partial and simultaneous assessments. Results reveal that organizational culture (X1) has a positive partial and simultaneous influence on employee performance (Y). However, interpersonal communication (X2) does not exhibit a partial or simultaneous impact on employee performance (Y). Notably, both organizational culture (X1) and interpersonal communication (X2) variables positively influence employee performance (Y) when considered both partially and simultaneously.